IL-17 promotes keratinocyte proliferation via the downregulation of C/EBPα - MA, WEI-YUAN; JIA, KUN; ZHANG, YAN (Experimental and therapeutic medicine, 2016)
Psoriasis vulgaris is a common chronic inflammatory skin disease characterized by the hyperproliferation and abnormal differentiation of keratinocytes. CCATT/enhancer binding protein α (C/EBPα) is abundant in the epidermis and is associated with the proliferation of keratinocytes. However, the role of C/EBPα in the proliferation of keratinocytes and the pathogenesis of psoriasis vulgaris are yet to be elucidated. In the present study, using two-step immunohistochemistry, the expression levels of C/EBPα and Ki-67 were examined in skin biopsies harvested from 30 patients with psoriasis vulgaris and 30 healthy control subjects. The proliferation index (PI) was calculated and the correlation between C/EBPα expression levels and the PI was assessed using Pearson's correlation coefficient. In addition, the effect on HaCaT immortalized human keratinocytic cells of treatment with various concentrations of interleukin (IL)-17 was investigated. Subsequently, cell proliferation rates were examined using a Cell Counting kit-8 assay and the mRNA and protein expression levels of C/EBPα were analyzed using semiquantitative reverse transcription-polymerase chain reaction and western blotting, respectively, in order to analyze the effects of IL-17 stimulation on C/EBPα expression levels. C/EBPα expression was predominantly detected in the cytoplasm of the keratinocytes and C/EBPα expression levels were significantly lower in the psoriatic lesions (P<0.05), as compared with the control group. An inverse correlation was detected between the expression levels of C/EBPα and the PI in the psoriatic lesions. Furthermore, a significant increase in the cell proliferation rate and significant reductions in the mRNA and protein expression levels of C/EBPα were detected in HaCaT cells following treatment with IL-17. These results demonstrated that C/EBPα may act as a downstream target of IL-17 and may be associated with the pathogenesis of psoriasis.